THE NEEDS ASSESSMENT FOR ENGLISH WRITING COMPETENCY OF STUDENTS IN DEPARTMENT OF EDUCATION AT PHRANAKHON SI AYUTTHAYA RAJABHAT UNIVERSITY - Tantichat , Narumon; Masoot, Wanvisa (Journal of Liberal Art of Rajamangala University of Technology Suvarnabhumi, 2025)
The purpose of this research was to assess the needs for the development of English writing skills of students in the Faculty of Education, Phranakhon Si Ayutthaya Rajabhat University. This study employed a survey research methodology. The data collection instruments consisted of a needs assessment form for developing English writing skills and topics for group discussion. The statistics used for data analysis included finding the priority needs index by finding the PNI modified through Microsoft Excel for calculation and analyzing the content of the data from the group discussion. The research results found that the top 3 issues that students needed to develop their writing skills the most from the questionnaire on needs and focus group discussions were: choosing correct and appropriate vocabulary, using correct and appropriate grammar, and spelling words correctly. In addition, the 3 groups of students suggested ways to solve these problems to effectively develop their writing skills differently as follows: the group of students with low language ability wanted to learn both vocabulary and basic structures through teacher-assigned tasks. The group of students with moderate language ability expressed the view that learning vocabulary and structures through context from reading texts related to the topic to be written could help solve their problems in choosing appropriate words and structures. In addition, having leading questions in writing could help improve writing and sequencing. The group of students with high language ability stated that writing skills would be developed effectively if they received study of various writing styles and feedback from the teacher.